2020
DOI: 10.1093/nar/gkaa832
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 infection activates endogenous retroviral promoters regulating antiviral gene expression

Abstract: Although endogenous retroviruses (ERVs) are known to harbor cis-regulatory elements, their role in modulating cellular immune responses remains poorly understood. Using an RNA-seq approach, we show that several members of the ERV9 lineage, particularly LTR12C elements, are activated upon HIV-1 infection of primary CD4+ T cells. Intriguingly, HIV-1-induced ERVs harboring transcription start sites are primarily found in the vicinity of immunity genes. For example, HIV-1 infection activates LTR12C elements upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 97 publications
2
61
4
Order By: Relevance
“…Notably, GBP2 and GBP5 targeted only highly pathogenic avian influenza viruses harboring a furin cleavage site in their hemagglutinin [ 46 , 47 ]. A recent study also showed that GBP2 and GBP5 suppressed furin-mediated maturation of the envelope protein of human endogenous retrovirus K [ 48 ] (Fig. 1 b).…”
Section: Antiviral Gbpsmentioning
confidence: 70%
“…Notably, GBP2 and GBP5 targeted only highly pathogenic avian influenza viruses harboring a furin cleavage site in their hemagglutinin [ 46 , 47 ]. A recent study also showed that GBP2 and GBP5 suppressed furin-mediated maturation of the envelope protein of human endogenous retrovirus K [ 48 ] (Fig. 1 b).…”
Section: Antiviral Gbpsmentioning
confidence: 70%
“…These two GTPases exert broad antiviral activity by inhibiting the virus-dependency factor furin (109). Intriguingly, numerous LTR12C and related LTR12D elements are activated upon HIV-1 infection (107,110), suggesting that they may be part of a larger network regulating antiviral immune responses. In line with this, expression of an LTR12C-SEMA4D fusion transcript is also increased in HIV-1 infected cells (107).…”
Section: Exogenous Retroviruses Harbor Multiple Binding Sites For Cellular Transcription Factors In Theirmentioning
confidence: 99%
“…Intriguingly, numerous LTR12C and related LTR12D elements are activated upon HIV-1 infection (107,110), suggesting that they may be part of a larger network regulating antiviral immune responses. In line with this, expression of an LTR12C-SEMA4D fusion transcript is also increased in HIV-1 infected cells (107). SEMA4D (also called CD100) is a regulator of B cell activation and may contribute to T cell senescence in HIV-1 infected individuals (111,112).…”
Section: Exogenous Retroviruses Harbor Multiple Binding Sites For Cellular Transcription Factors In Theirmentioning
confidence: 99%
See 2 more Smart Citations